I am Sam - Herskovitz, Marshall; Johnson, Kristine; Nelson, Jessie; Penn, Sean, 1960-; Pfeiffer, Michelle, 1957-; Fanning, Dakota, 1994-; Davis, Elliot; Chew, Richard; Powell, John, composer; Bedford Falls Productions; New Line Cinema Corporation; Red Fish, Blue Fish Films (Firm); et al. ([Calif.?] : New Line Home Entertainment, 2002)
Sam Dawson has the mental capacity of a 7-year-old. He works at a Starbucks, is obsessed with the Beatles and has a daughter with a homeless woman who abandons them. As the daughter reaches age 7, Sam's limitations start to become a problem. When the authorities take his daughter away, Sam shames a high-priced lawyer into taking his case pro bono. In the process, he teaches her a great deal about love, and whether it's really all you need.
DVD; 5.1 Dolby digital, DTS surround and stereo surround sound.
Requirements to access DVD-ROM features: PC with a DVD-ROM drive with a DVD decoder installed, Windows 95 or higher with Internet Explorer 5.0 or higher. Some of the DVD-ROM features may not work on a Macintosh. Internet access may be required for certain features.
Closed-captioned.
Sean Penn, Michelle Pfeiffer, Dakota Fanning.
Cinematography, Elliot Davis; editor, Richard Chew; music, John Powell; director of photography, Elliot Davis.
MPAA rating: PG-13.
Keywords: People with mental disabilities -- Drama; Custody of children -- Drama; Feature films; Video recordings for the hearing impaired